A SPR aptamer sensor for mercury based on AuNPs@NaYF4:Yb, Tm, Gd upconversion luminescent nanoparticles. Issue 42 (23rd October 2017) - Ling, Bo; Ma, Yuanhui; Chen, Hongqi; Wang, Lun
Abstract : A new aptamer-based surface plasmon resonance system has been designed to detect Hg 2+ that utilizes gold nanoparticle coated NaYF4 :Yb, Tm, Gd near-infrared upconversion nanoparticles as probes. Abstract : A new aptamer-based surface plasmon resonance (SPR) system has been designed to detect Hg 2+ that utilizes near-infrared (NIR)-to-NIR gold nanoparticle coated NaYF4 :Yb, Tm, Gd up-conversion nanoparticles (AuNPs@NaYF4 :Yb, Tm, Gd UCNPs) as probes. The AuNPs@NaYF4 :Yb, Tm, Gd UCNPs were prepared and excited by near-infrared light (980 nm) which emitted at a near-infrared wavelength (808 nm) using an inexpensive infrared continuous wave laser diode. The AuNPs@NaYF4 :Yb, Tm, Gd UCNPs were conjugated with Hg 2+ aptamers. In the presence of Hg 2+, the AuNPs@NaYF4 :Yb, Tm, Gd UCNPs were brought into close proximity because of the formation of T–Hg 2+ –T base pairs. Then the luminescence enhanced because of the plasmon resonance effects. Based on this, a new SPR system was developed for the detection of Hg 2+ that had high sensitivity and selectivity in the NIR region. This method was successfully applied to detect Hg 2+ concentration in real samples.